Dufour and Soret effects on pulsatile hydromagnetic flow of Casson fluid in a vertical non-Darcian porous space - Srinivas, Suripeddi; Kumar, Challa Kalyan; Reddy, Anala Subramanyam (Nonlinear Analysis: Modelling and Control, 2022)
This article aims to inspect the pulsating hydromagnetic slip flow of Casson fluid in a vertical porous channel with heat and mass transfer. The fluid is injected into the channel from the left wall and removed at the opposite wall with the same velocity. The impact of non-Darcy, Soret, and Dufour effects are taken under consideration. The governing partial differential equations (PDEs) are converted to ordinary differential equations (ODEs) using perturbation method and solved by utilizing 4th-order Runge–Kutta (R–K) technique together with shooting method. The impact of dissimilar parameters on flow, heat and mass transfer characteristics are displayed and discussed.
Keywords: Casson fluid; slip parameter; pulsatile flow; convective boundary; Dufour and Soret effects